The Mahabharata as a Strategic Guide: Exploring its Relevance to Modern Principles of War - Chand, Deergh Bahadur (Unity Journal, 2026)
The Mahabharata narrates events and aftermath of the Kurukshetra War, which revolves around perpetual conflict between good and evil, represented by the Pandava and Kaurava brothers of the legendary Bharata dynasty, respectively. The article explores how The Mahabharata, with a profound repository of prudent thoughts and battle tactics, serves as a strategic guide for the military, presenting insights that align with modern principles of war. The Kurukshetra War, the central conflict in the Sanskrit epic, offers a plenitude of strategic lessons that reverberate with modern military doctrines and principles outlined by theorists like Carl von Clausewitz and Sun Tzu. Using comparative and descriptive analysis of secondary sources, the research investigates key strategic dimensions such as Shalya's implementation of psychological warfare tactics, Lord Krishna's exemplary war leadership apparent in his strategic counsel, including the Bhagavad Gita discourse, Guru Drona's sophisticated battle formations (Vyuha Rachana), and Bheeshma Pitamah's application of proportional force through controlled engagement, and strategic exclusion of Karna from combat operations. Lord Krishna’s diplomatic maneuvers and tactical propaganda emulate modern‑day asymmetric warfare and intelligence operations. Dharma Yuddha (righteous war) perception is scrutinized in the context of just war theory, highlighting ethical dilemma that persistently challenges contemporary military leaders. These strategies are analyzed for their theoretical foundations and practical applications within the context of ancient Eastern military doctrine. In doing so, the study explores lessons on leadership motivation, ethical decision‑making, and the strategic relevance of war, positioning it as a substantial resource for military scholars, strategists, and policymakers.